ANALYSIS OF STUDENT PROFESSIONALISM IN TERMS OF ATTENDANCE LEVEL IN SCHOOL FIELD INTRODUCTION (SFI) ACTIVITIES - Dedi Riyan Rizaldi Rizaldi (Balai Diklat Keagamaan Denpasar, 2023)
School Fields Introduction (SFI) is one of the courses that aims to provide an overview or initial introduction to students regarding how to be a good teacher. This study aims to determine the professionalism of SFI students in terms of attendance levels during the SFI activity process. The method used in this research is descriptive and qualitative and involves observation, interviews, and direct viewing of data in the field. The subjects in this study were 8 SFI students and 1 teacher coordinator from MA Plus Nurul Islam Sekarbela. Data obtained through the processes of observation and interviews were analyzed descriptively in the form of paragraphs. Based on the research that has been done, it is found that the level of student professionalism in terms of attendance is still very minimal, with a percentage of 38%, or only 3 out of 8 students. In addition, it was found that the level of attendance had a good correlation with the acquisition of the final grades of students, where the higher the level of attendance, the higher the value obtained.